2019
DOI: 10.1007/s00220-019-03609-y
|View full text |Cite
|
Sign up to set email alerts
|

Black Holes and Higher Depth Mock Modular Forms

Abstract: By enforcing invariance under S-duality in type IIB string theory compactified on a Calabi-Yau threefold, we derive modular properties of the generating function of BPS degeneracies of D4-D2-D0 black holes in type IIA string theory compactified on the same space. Mathematically, these BPS degeneracies are the generalized Donaldson-Thomas invariants counting coherent sheaves with support on a divisor D, at the large volume attractor point. For D irreducible, this function is closely related to the elliptic genu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(87 citation statements)
references
References 69 publications
5
82
0
Order By: Relevance
“…We note that a similar phenomenon arises in the context of N = 2 black holes [27,28], but in that context mock modular forms of higher depth are expected to arise due to the occurrence of BPS bound states involving an arbitrary number of constituents [29,30]. In this paper, inspired by earlier work [31,32] in the context of N = 2 black holes, we attempt to give a physical justification of this non-holomorphic correction from the macroscopic point of view in the N = 4 context, by computing the contribution of the continuum of scattering states in the quantum mechanics of two-centered BPS black holes.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…We note that a similar phenomenon arises in the context of N = 2 black holes [27,28], but in that context mock modular forms of higher depth are expected to arise due to the occurrence of BPS bound states involving an arbitrary number of constituents [29,30]. In this paper, inspired by earlier work [31,32] in the context of N = 2 black holes, we attempt to give a physical justification of this non-holomorphic correction from the macroscopic point of view in the N = 4 context, by computing the contribution of the continuum of scattering states in the quantum mechanics of two-centered BPS black holes.…”
Section: Introductionmentioning
confidence: 59%
“…In Section 4.5 we computed the index using localization, and found that the result (4.23) contains both a term proportional to the complementary error function, also present in [32], as well as a Gaussian term, which is in fact necessary for the modular covariance of the generating function of MSW invariants [27,28]. It would be interesting to apply similar localization techniques to the case of multi-centered black holes, where mock modular forms of higher depth are expected to occur [30]. Interestingly, such modular objects arise in the computation of elliptic genera of squashed toric manifolds [54], and presumably also in the context of higher rank monopole moduli spaces, which may provide a useful model for the dynamics of multi-centered black holes.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to find relations (dualities) to other physics problems where similar modular structures appeared, e.g. [88,[99][100][101][102].…”
Section: Discussion and Open Questionsmentioning
confidence: 99%
“…Since the latter are invariant under spectral flow, the resulting partition function can still be formally decomposed as a sum of indefinite theta series, with a kernel given by a sum over flow trees [36,17]. While the convergence and modular properties of this theta series are by now well understood when the reducible divisor D is the sum of two components [36,40], the representations of the tree index found in this paper will be instrumental in extending these results to a general reducible divisor [41].…”
Section: Introductionmentioning
confidence: 88%
“…The two representations may be useful for different purposes. For instance, the second representation is suitable for the proof of convergence of the BPS partition function, whereas the first representation is more convenient for analyzing its modular properties [41], this is why we give here both of them. Since their proofs are essentially identical, we only present the proof for the first representation.…”
Section: )mentioning
confidence: 99%